Functionalized triazolopeptoids – a novel class for mitochondrial targeted delivery. Issue 14 (5th March 2015) - Althuon, Daniela; Rönicke, Franziska; Fürniss, Daniel; Quan, Jasmin; Wellhöfer, Isabelle; Jung, Nicole; Schepers, Ute; Bräse, Stefan
Abstract : Here we introduce linear 1, 4-triazolopeptoids as a novel class of cell penetrating peptidomimetics suitable as organ targeting molecular transporters of bioactive cargo. Abstract : Here we introduce linear 1, 4-triazolopeptoids as a novel class of cell penetrating peptidomimetics suitable as organ targeting molecular transporters of bioactive cargo. Repetitive triazole moieties with up to three residues were assembled on solid supports using copper-catalyzed alkyne–azide cycloadditions (CuAAC) in a submonomer approach. Depending on the lipophilicity of their side chain appendages the 1, 4-triazolopeptoids showed either endosomal localization or a strong colocalization with the mitochondria of HeLa cells with moderate toxicity. While the basic triazolopeptoids mainly target the neuromast cells in zebrafish embryos, the lipophilic ones colocalize with either cartilage in the jaws and the blood vessel system.